Myth, Materiality, and Lived Religion In Merovingian and Viking Scandinavia - Wikström af Edholm, Klas; Jackson Rova, Peter; Nordberg, Andreas; Sundqvist, Olof; Zachrisson, Torun (Stockholm Studies in Comparative Religion, 2019)
"The authors of the present volume, Myth, Materiality, and Lived Religion, focus on the material dimension of Old Norse mythology and the role played by myths in everyday life. More broadly expressed, the collection looks at the social, ceremonial and material contexts of myths. This topic has been underexplored in previous research on Old Norse myths, despite its important theoretical implications. However, discussions around materiality, in a more general sense, have for a long time been significant for historians of religion, especially archaeologists. Myth, Materiality, and Lived Religion seeks to make the case for the relevance of materiality to literary historians and philologists as well. Questions relating to the theme of materiality and lived religion are posed in this book, including: • What do myths tell us about the material culture of the periods in which they were narrated? • What role did myths or mythical beings play in connection to, for instance, illnesses and remedies during the Viking Period and the Middle Ages? • How did ordinary people experience participation in a more formal sacrificial feast led by ritual specialists? The editors of this book are all associated with the Department of Ethnology, History of Religions and Genders Studies at Stockholm University, Sweden."